An Analysis of EFL Students’ Descriptive Writing Ability - Muhammad Makmun Mi’raj; Sabarun Sabarun; Zaitun Qamariah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
This research was meant to describe students' descriptive writing abilities. The sample of this research were 25 second semester students of English education study program of IAIN Palangka Raya who were chosen using random sampling technique. This research is descriptive research. Then, a descriptive text writing test was used to measure the students' ability in writing descriptive text. Vocabulary, mechanics, and organization are the three key areas on which students' abilities to write descriptive writings are being concentrated. While the final ability of students in writing descriptive texts is categorized into five levels; very good, good, average, fair, bad. The findings revealed that the students generally had a score of 66 for writing descriptive text, which was considered to be good. Meanwhile, three components that researcher focused on in writing descriptive text; Student's vocabulary score is 77 categorized in good level, Student's mechanics score is 63 categorized in good level, and students' organization score is 63 categorized or in good level.